Challenge of Gender Role Reversal in Naomi Alderman's The Power - Safitri, Alya Nur; Marsih, Linusia (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This study aims to investigate the gender role reversal reflected in Naomi Alderman's The Power and its impacts on societal structure. In conducting the study, V. Geetha's theory of gender role reversal is employed. Moreover, this research is designed as descriptive qualitative research because the data are in the form of words, and the analysis results are described using rich, detailed, and descriptive language to capture the complexity. In addition, gender study is applied since the study deals with gender issues. The results of the study show that as women are empowered with physical strength through the 'skein' of new organs in the female body, they take over the roles that men have. The women take over the roles of leaders in society and institutions. This reversal of gender roles has significant impacts on society. The women use their power by legalizing injustice such as men being mistreated by governments, and impose restrictions on men's rights to act and behave in society. In addition, the gender role reversal leads to international conflicts such as war in some countries and terrorism. This research highlights that when women have more power and dominance in society, the social structure changes. Keywords: gender role reverse, leader, patriarchy, power, society